Early life origins of chronic obstructive pulmonary disease. Issue 1 (2nd September 2009) - Svanes, C; Sunyer, J; Plana, E; Dharmage, S; Heinrich, J; Jarvis, D; de Marco, R; Norbäck, D; Raherison, C; Villani, S; Wjst, M; Svanes, K; et al.
Abstract : Background: Early life development may influence subsequent respiratory morbidity. The impact of factors determined in childhood on adult lung function, decline in lung function and chronic obstructive pulmonary disease (COPD) was investigated. Methods: European Community Respiratory Health Survey participants aged 20–45 years randomly selected from general populations in 29 centres underwent spirometry in 1991–3 (n = 13 359) and 9 years later (n = 7738). Associations of early life factors with adult forced expiratory volume in 1 s (FEV1 ), FEV1 decline and COPD (FEV1 /FVC ratio <70% and FEV1 <80% predicted) were analysed with generalised estimating equation models and random effects linear models. Results: Maternal asthma, paternal asthma, childhood asthma, maternal smoking and childhood respiratory infections were significantly associated with lower FEV1 and defined as "childhood disadvantage factors"; 40% had one or more childhood disadvantage factors which were associated with lower FEV1 (men: adjusted difference 95 ml (95% CI 67 to 124); women: adjusted difference 60 ml (95% CI 40 to 80)). FEV1 decreased with increasing number of childhood disadvantage factors (⩾3 factors, men: 274 ml (95% CI 154 to 395), women: 208 ml (95% CI 124 to 292)). Childhood disadvantage was associated with a larger FEV1 decline (1 factor: 2.0 ml (95% CI 0.4 to 3.6) per year; 2 factors: 3.8 ml (95% CI 1.0 to 6.6); ⩾3 factors: 2.2 ml (95% CI −4.8 to 9.2)). COPD increased with increasing childhood disadvantage (1 factor, men: OR 1.7 (95% CI 1.1 to 2.6), women: OR 1.6 (95% CI 1.01 to 2.6); ⩾3 factors, men: OR 6.3 (95% CI 2.4 to 17), women: OR 7.2 (95% CI 2.8 to 19)). These findings were consistent between centres and when subjects with asthma were excluded. Conclusions: People with early life disadvantage have permanently lower lung function, no catch-up with age but a slightly larger decline in lung function and a substantially increased COPD risk. The impact of childhood disadvantage was as large as that of heavy smoking. Increased focus on the early life environment may contribute to the prevention of COPD.